The combined effect of sowing methods and nitrogen rates on wheat yield and regulation of soil water consumption in Loess Plateau - Noor, Hafeez; Shahbaz, Khan; Sanaullah; Shah, Syed Ahmed; Anwar, Sumera; Min, Sun; Zhiqiang, Gao (International Journal of Applied and Experimental Biology, 2023)
Field experiments were conducted to assess the effect of four sowing methods on the growth, photosynthetic, and yield traits of dryland winter wheat. Furthermore, the impact of N input rates was also evaluated on water consumption by the wheat plants from the soil. The seeds of winter wheat were sown using wide space sowing (WS), furrow sowing (FS), stereoscopic sowing (SS), and drill sowing (DS). The results indicated that different sowing methods significantly affected the yield and grain quality. The increase in grain yield was 25%, 17%, and 11%, respectively, under WS, FS, and SS compared to that in DS. From sowing to jointing, the water consumption was highest under WS, mainly in deep soil layers. The photosynthetic traits and leaf area index were highest under WS, followed by those under FS. The plant height was highest under DS. The water consumption index and grain yield were higher at the N rate 210-240 kg ha-1 than those at the other N rates applied. In conclusion, the WS and 210 kg N ha-1 improved the canopy structure, water consumption, and winter wheat yield.